Analisis Kebutuhan Layanan Bimbingan Karier Wirausaha dalam Mendukung Implementasi Kurikulum Merdeka - Nur, Edil Wijaya; Saman, Abdul; Buchori, Sahril (Islamic Counseling: Jurnal Bimbingan Konseling Islam, 2024)
This study aims to identify the needs of high school students for entrepreneurial career guidance to support the implementation of the Merdeka Curriculum. A descriptive quantitative approach with a survey model was employed, involving 30 randomly selected students from a high school in Sidrap Regency. The survey questionnaire was validated by experts and distributed online via Google Forms. The validity and reliability tests indicated that all items in both questionnaires were valid for use. Data analysis utilized the general percentage formula for Respondent Achievement Level (RAL). As shown in Table 1, students indicated a preference for E-Modules (90%), followed by projects or simulations (82%), and social media (70%). According to Table 2, students were interested in content such as success stories of young entrepreneurs (92%), the importance of entrepreneurial spirit (86%), and key entrepreneurial concepts (86%). These findings provide guidance for counseling teachers to develop E-Module products that include young entrepreneur success stories, the importance of entrepreneurship, key entrepreneurial concepts, and utilize social media support as well as project or simulation-based evaluations in entrepreneurial career guidance.